A nagyszebeni jogakadémia hallgatóinak kérelme az oktatás megreformálása tárgyában 1848 májusából - P. Szabó, Béla (Gerundium, 2019)
The Request for Educational Reform of the Students of the School of Law in Nagyszeben of May 1848. In spring 1848 amidst the zeal of the revolution started in almost all of the higher educational institutions in Hungary and Transylvania student movements to reform education in the institutions. In May 1848 the students of the Law School of the Saxons in Transylvania at Nagyszeben also submitted an application through the institution’s Senate to the sustaining Lutheran Church including – among others – the following issues: guaranteeing the freedom to education and teaching, reforming the study and exam system, significantly developing the substance of the library, getting the right to meet and vote for the students’ representatives during procedures against students; reviewing the academy’s disciplinary regulation. The following source-presentation – besides the Hungarian translation of the request – explains the circumstances of origin and the afterlife of the application.